Bernard Shaw and Modern Advertising Prophet Motives - Wixson, Christopher (Bernard Shaw and His Contemporaries, 2018)
This book charts how promotional campaigns in which Bernard Shaw participated were key crucibles within which agency and personality could re-negotiate their relationship to one another and to the consuming public. Concurrent with the rise of modern advertising, the creation of Shaw's 'G.B.S.' public persona was achieved through masterful imitation of patent medicine marketing strategies and a shrewd understanding of the relationship between product and spokesman. Helping to enhance the visibility of his literary writing and dovetailing with his Fabian political activities, 'G.B.S.' also became a key figure in the evolution of testimonial endorsement and the professionalizing of modern advertising. The study analyzes multiple ad series in which Shaw was prominently featured that were occasions for self-promotion for both Shaw and the agencies, and presage the iconoclastic style of contemporary 'public personality' and techniques of celebrity marketing.